Korelasi Kemampuan Membaca Kritis dengan Kemampuan Mengungkapkan Makna Tersirat Teks Berita Online pada Siswa Kelas VII di SMP Negeri 2 Sungguminasa - Khasanah, Nurul; Anshari, Anshari; Nurhusna, Nurhusna (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
Critical reading skills are an important ability to understand explicit and implicit information in digital news texts that are loaded with facts and opinions. This study aims to determine the relationship between critical reading skills and the ability to express the meaning implied in online news texts in grade VII students of SMP Negeri 2 Sungguminasa. The research method used is a quantitative method with a correlational design. The research sample consisted of 31 students in grades VII-3 who were selected using the purposive sampling technique. The research instrument is in the form of an essay test which is used to measure critical reading ability and the ability to express implicit meaning. Data collection techniques are carried out through observation, written tests, and documentation. The data obtained were analyzed using descriptive statistics and Spearman correlation test. The results of the analysis showed a correlation coefficient of 0.9998 with a tcal value of 267.988 which was greater than the ttable value at the significance level of 5% or 1%. The findings show that there is a very strong and significant relationship between critical reading skills and the ability to express implicit meanings in online news texts. Thus, the results of this study confirm the importance of learning critical reading in improving students' ability to understand texts in depth.